Defesas do executado na execução fundada em título extrajudicial com previsão de convenção de arbitragem - Rizzo, Giovanna de Almeida (2014)
This paper approaches the defensive measures available to a debtor in a lawsuit that seeks the enforcement of an extrajudicial executive title that stipulates an arbitration clause as a means of conflict resolution. Firstly, it was performed an analysis of the expedited collection proceeding and the necessity of the obligation owed to be quantified, certain and enforceable. In addition to that, this paper deals with the existence of an arbitration agreement in the executive instrument and its effects. Lastly, the possible defenses of the debtor regarding the collection proceeding of an extrajudicial executive instrument are presented, as well as the jurisdiction responsible to resolve the conflict and the proceedings to be followed in each case